AN INSIGHTFUL EXPLORATION ON THE ACHIEVEMENT OF THE SUSTAINABLE RURAL DEVELOPMENT GOALS. A STUDY CASE- VALEA LUPULUI COMMUNE, IASI COUNTY, ROMANIA - Roxana Mihaela BOLOHAN (COCIORVĂ); Ramona Vasilica BACTER; Ioana BOLOHAN; Gavril ȘTEFAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aims to comprehensively examine the critical role of rural development in the broader framework of achieving the Sustainable Development Goals (SDGs). Employing a robust mixed-methods research design, we explore global and regional rural development policies through a cross-cutting analysis. The primary objective is to uncover the profound and positive impact of specific interventions on critical SDG indicators, with a particular focus, on poverty reduction, improved access to education and healthcare, and significant progress in agricultural productivity. Our research uses a mixed-methods design, combining quantitative analysis, qualitative insights from community engagement sessions, and spatial analysis using GIS-based mapping. Preliminary results show a promising correlation between sustainable agricultural practices and meeting the SDGs, with a 30% reduction in food insecurity rates, while the qualitative insights indicate a notable increase in community cohesion and empowerment, highlighting the impact of rural development on well-being. Summarising these multi-faceted findings, our study highlights the symbiotic relationship between rural development initiatives and the SDGs. The imperative for context-specific and adapted strategies is evident from the spatial analyses, highlighting the need for a comprehensive, integrated and locally informed approach to achieve sustainable and equitable overall development. The paper advocates the recognition of rural development as a key driver for positive change in pursuit of the SDGs, providing valuable insights for policy makers, practitioners and researchers.